Electronic Medical Record Implementation for Regional-based Disease Trend Analysis in Semarang City - Suhito, Hanif Pandu; Raniasmi, Prahita Indriana; Sholikun, Sholikun (Universitas Muhammadiyah Sidoarjo, 2024)
Electronic medical records (SIMPUS) has been implemented since 2019 in Semarang City, enabling community health centers to store patient medical data efficiently. Decision-making in disease control must be based on data and evidence-based approaches. The objective of this study is to display trends of disease based on visits to health centers in Semarang City. Using data from routine services provided by 37 health centers (Puskesmas) from 2020 to June 2024, a total of 8.669.287 patients were included. A quantitative descriptive analysis approach was used to determine the distribution of disease based on top 10 diagnoses, age groups, districts, and time periods. The results show that Acute upper respiratory infections of multiple and unspecified sites (J06) have increased and become top rank in the last three years. Hypertension (I10) also increased with the number of cases still high as runner up. Most of the cases in the top 10 diseases increase in number of cases from year to year. The sub-district of Tembalang, Semarang Barat, and Pedurungan tend to have the highest number of patient visits. Based on age groups, the most frequent visits to the health center are adults and pre-elderly groups, followed by teenagers and toddlers. This is related to the types of cases that are most often found. This trend analysis can be used to determine changes in patient visit patterns at Semarang community health centers from year to year and can help in comparing morbidity rates so it can help in determining health policy in Semarang.